Literary readings and discussions with Wilfried N'Sondé and Kangni Alem (Workshop Slave Trade Memories, 2023)
Slavery in history, memory and literature: an African perspective As part of the workshop "Slave Trade Memories at the Crossroads of Literature, Performance and History" in June 2022 the Africa Cluster of Excellence hosted this reading and discussion with Wilfried N'Sondé and Kangni Alem at @kunst-undkulturhausneunein8931. The event was moderated by Josias Semujanga and Thierry Boudjekeu. Born in Lomé, Togo, in 1966, Kangni Alem is a writer, translator and literary critic, playwright, art collector and exhibition curator, director of the "Atelier Théâtre de Lomé" founded by him in 1989. He has received numerous awards, including the Grand prix littéraire d'Afrique noire for his book Cola Cola jazz, the Tchicaya U'Tamsi Prize of the Concours Théâtral Interafricain for his play Chemins de Croix and more recently the 3rd Prize of the Williams Sassine Literary Prize for his short story Une histoire américaine. He is an associate researcher at the CELFA (Centre d'Études Linguistiques et Littéraires Francophones et Africaines) at the University of Bordeaux III and is currently editor-in-chief of the review Notre Librairie and translator of the writer Ken Saro-Wiwa. Kangni Alem is a lecturer in comparative literature and theatre pedagogy at the University of Lomé. He directs the professional Master's programme, and has been working for the last few years on the mediation between literature, visual arts and performance. Wilfried N’Sondé is a prolific writer, musician, author and composer. Born in 1968 in Brazzaville, he studied political science in Paris before moving to Berlin, where he stayed for 25 years. He now lives in Lyon. In 2016, he taught literature at the University of Bern as a visiting professor. He is currently a lecturer at the University of Mayotte. As a writer, he publishes his work with Actes Sud, and his novels have been translated into several languages. He has won several renowned awards, including the Prix des Cinq Continents de la Francophonie and the Prix Senghor de la création littéraire for Le Cœur des enfants léopards (2007), the Prix Ahmadou Kourouma for Le silence des esprits. And numerous other awards for Fleur de béton (2012) and Berlinoise (2015) and Un océan, deux mers, trois continents (2018). His most recent novel is entitled Femme du ciel et des tempêtes.